Dynamic Modeling of a Hybrid Propulsion System for Tourist Boat - Linda Barelli; Gianni Bidini; Federico Gallorini; Francesco Iantorno; Nicola Pane; Panfilo Andrea Ottaviano; Lorenzo Trombetti (Energies, 2018)
Interest in designing more efficient and versatile ships comes from increasingly stringent regulations on emissions. In this context, a possible solution to overcome these limits may be the replacement of marine propulsion systems based on diesel engines with hybrid architectures. This paper provides a dynamic analysis of a hybrid marine propulsion system (HPS) consisting of an internal combustion engine and an electric engine coupled with a battery pack. A dynamic simulation of a daily working cycle was carried out based on a real load demand. The instantaneous behavior of each component was evaluated. A brief summary of the HPS performance, varying the battery pack capacity, was provided together with an estimation of its impact on the system efficiency. Referring to this last point, the adoption of a hybrid system has permitted a decrease in the specific consumption, on a given route, of about 2% with respect to the case where the propulsion is entrusted only to the diesel engine.